Quantum dot composition, method for manufacturing same, cured film thereof, and light-emitting element and display device including same

By developing quantum dot compositions suitable for EHD inkjet printing, the problem of difficult application of high viscosity quantum dot compositions in the prior art is solved, and the preparation and application of quantum dot compositions with high viscosity and excellent optical properties is realized, which is suitable for the manufacturing of display devices.

CN119775992APending Publication Date: 2025-04-08SAMSUNG ELECTRONICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411366266.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-04
Filing Date
2024-09-29
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing inkjet printing technology is difficult to effectively use high viscosity quantum dot compositions, especially in electrohydrodynamic (EHD) inkjet printing, and the low viscosity of the quantum dot compositions limits its application.

Method used

A quantum dot composition including quantum dots, photopolymerizable monomers and oligomers was developed to produce quantum dot compositions with high viscosity (about 100 cp to 1000 cp) and excellent optical properties suitable for EHD inkjet printing by surface modification and dispersion techniques.

Benefits of technology

The possibility of using high viscosity quantum dot compositions in EHD inkjet printing is realized, and the ink ejection capability and optical performance is improved, suitable for the manufacturing of display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066310030000081
    Figure BDA0005066310030000081
  • Figure BDA0005066310030000091
    Figure BDA0005066310030000091
  • Figure BDA0005066310030000141
    Figure BDA0005066310030000141
Patent Text Reader

Abstract

Provided are a quantum dot composition, a method of manufacturing the same, a cured film thereof, and a light-emitting element and a display device including the same, particularly a quantum dot composition for electrohydrodynamic ink jet printing, a method of manufacturing the same, a cured product thereof, and a display device including the same. The quantum dot composition comprises quantum dots; a photopolymerizable monomer; and an oligomer, wherein the photopolymerizable monomer includes a compound including an aromatic ring.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is based on and claims the benefit of priority from Korean Patent Application No. 10-2023-0131930 filed on October 4, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field

[0003] The present disclosure relates to a quantum dot composition, a method for manufacturing the same, a cured product thereof, and a display device comprising the same, and more particularly to a quantum dot composition for electrohydrodynamic (electrohydrodynamic) inkjet printing, a method for manufacturing the same, a cured product thereof, and a display device comprising the same. Background Art

[0004] Quantum dots or QDs (so-called semiconductor nanocrystals) produce multiple colors by emitting light of different wavelengths depending on particle size and without changing the material type. Quantum dots have attracted much attention as next-generation light-emitting elements due to their ability to provide superior color purity and photostability compared to known light-emitting materials.

[0005] Recently, quantum dots have become a new trend in the field of displays such as TVs and LEDs and electronic devices in a composite form when dispersed in a polymer matrix. Quantum dots, such as those formed from cadmium-selenium (CdSe) and indium-phosphorus (InP), have rapidly developed in terms of quantum yield, and their synthesis methods for obtaining quantum yields close to 100% are being introduced. Based on this, TVs including quantum dot sheets are currently being commercialized.

[0006] In the next step of manufacturing, it is expected that a self-emitting version will be provided for quantum dot TVs, rather than using the method of filtering with a color filter layer that has been developed by adding quantum dots to the color filter layer of conventional LED TVs (i.e., and by excluding pigments and dyes). The core technology for developing quantum dot TVs focuses on the duration of the maintenance of the light efficiency of quantum dots during the process of forming pixels using quantum dots and during the manufacturing process.

[0007] At the same time, the material used for the color filter is required to have high sensitivity, adhesion to the substrate, chemical resistance, heat resistance, etc. The color filter applied to the conventional display is manufactured by forming a desired pattern through an exposure process by applying a photomask thereto using a photosensitive resist composition, and dissolving and removing the unexposed area through a development process. This process and other similar processes are often accompanied by increased costs due to waste materials.

[0008] Recently, a method of reducing the use of materials as much as possible and using materials only for desired areas, rather than patterning by conventional spin coating or slit coating, has attracted much attention to suppress the increase in manufacturing costs caused by high-quality materials used in pixels. The most representative inkjet methods are the bubble jet method and the piezoelectric method. Since the material is used only in the desired pixel, unnecessary waste of materials can be suppressed by the inkjet method.

[0009] However, a quantum dot composition for inkjet printing is required to have a viscosity of 100 centipoise (cp) or less, for example, 50 cp or less, and thus it is difficult to apply an ink having a high viscosity exceeding 100 cp or more thereto.

[0010] In order to overcome such disadvantages of inkjet printing, electrohydrodynamic (EHD) inkjet printing capable of fine patterning has been developed. The EHD inkjet method enables miniaturization and printing of ink according to an electric field by applying a potential difference between a nozzle ejecting ink and a substrate.

[0011] As a related art, a solution for an electrohydrodynamic printing method has been disclosed in Korean Patent Application Publication No. 10-2020-0137977. Summary of the invention

[0012] Provided are a quantum dot composition having high viscosity suitable for an EHD inkjet printing method, excellent optical properties, and excellent ink jetting ability (jetting performance), and a method for producing the same.

[0013] Also provided are a cured product of the quantum dot composition and a display device comprising the same.

[0014] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments of the disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The above and other aspects, features and advantages of some embodiments of the present disclosure will become more apparent from the following description considered in conjunction with the accompanying drawings, in which:

[0016] Figure 1 A flow chart showing a method of making a quantum dot composition; and

[0017] Figure 2 is a schematic diagram showing a light-emitting element of a display device including a quantum dot composition. DETAILED DESCRIPTION

[0018] The present disclosure will now be described more fully below with reference to the accompanying drawings, in which a variety of embodiments are shown. However, the present disclosure may be embodied in many different forms and should not be construed as being limited to the embodiments set forth herein. Rather, these embodiments are provided so that the content of the present disclosure will be thorough and complete and will fully convey the scope of the invention to those skilled in the art. The same reference numerals refer to the same elements throughout.

[0019] It will be understood that when an element is referred to as being “on” another element, it can be directly on the other element or intervening elements may be present therebetween. In contrast, when an element is referred to as being “directly on” another element, there are no intervening elements present.

[0020] It will be understood that although the terms "first", "second", "third", etc. can be used in this article to describe various elements, components (assemblies), regions, layers and / or parts, these elements, components (assemblies), regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish an element, component (assembly), region, layer or part from another element, component (assembly), region, layer or part. Therefore, without departing from the teachings herein, the "first element", "component (assembly)", "region", "layer" or "part" discussed below may be referred to as a second element, component (assembly), region, layer or part.

[0021] The terms used herein are only for the purpose of describing specific embodiments and are not intended to be restrictive. "One (kind) (indefinite article) (a, an)", "the (the)" and "at least one (kind)" used herein do not represent the limitation of quantity, and are intended to include both the singular and the plural, unless the context clearly indicates otherwise. For example, unless the context clearly indicates otherwise, "(a) element" has the same meaning as "at least one element". "At least one (kind)" should not be interpreted as limiting "one (kind)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. It will be further understood that the term "comprising" or "including" when used in this specification, indicates the existence of the stated features, regions, wholes, steps, operations, elements and / or components (assemblies), but does not exclude the existence or addition of one or more other features, regions, wholes, steps, operations, elements, components (assemblies) and / or their sets.

[0022] In addition, relative terms, such as "lower" or "bottom" and "upper" or "top", may be used herein to describe the relationship of one element to another element as shown in the figure. It will be understood that in addition to the orientation depicted in the figure, relative terms are also intended to cover different orientations of the device. For example, if the device in one of the figures is turned over, the element described as being on the "lower" side of the other element will be oriented on the "upper" side of the other element. Therefore, depending on the specific orientation of the figure, the term "lower" can cover both "lower" and "upper" orientations. Similarly, if the device in one of the figures is turned over, the element described as "below" or "below" the other element will be oriented "above" the other element. Therefore, the term "below..." or "below..." can cover both "above..." and "below..." orientations.

[0023] As used herein, "about" or "approximately" is inclusive of the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, 20%, 10%, or 5% relative to the stated value.

[0024] Throughout the disclosure, the expression "at least one of a, b, or c" refers to only a, only b, only c, both a and b, both a and c, both b and c, all of a, b, and c, or variations thereof.

[0025] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which this application belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, will not be interpreted in an idealized or overly formal sense unless clearly defined in this article.

[0026] In addition, throughout the specification, the term “comprising” an element specifies the presence of the stated elements, but does not exclude the presence or addition of one or more elements unless stated otherwise.

[0027] In addition, as used herein, the term "(meth)acrylate" refers to acrylate and methacrylate, the term "(meth)acrylic acid" refers to acrylic acid and methacrylic acid, and the term "(meth)acryloyl" refers to acryl and methacryloyl.

[0028] In the present disclosure, a monomer is distinguished from an oligomer and a polymer and refers to a compound having a weight average molecular weight of 1,000 or less. As used herein, the term "photopolymerizable monomer" refers to a compound participating in polymerization, such as a (meth)acrylate compound.

[0029] As used herein, the term "substituted" refers to the replacement of a hydrogen of a compound or functional group with a substituent selected from the group consisting of C1-C30 alkyl, C2-C30 alkenyl, C2-C30 alkynyl, C1-C30 alkoxy, C1-C30 heteroalkyl, C3-C30 heteroalkylaryl, C3-C30 cycloalkyl, C3-C15 cycloalkenyl, C6-C30 cycloalkynyl, C2-C30 heterocycloalkyl, halogen (-F, -Cl, -Br or -I), hydroxyl (-OH), nitro (-NO 2 ), cyano (-CN), ester (-C(=O)OR, wherein R is C1-C10 alkyl or alkenyl), ether (-OR, wherein R is C1-C10 alkyl or alkenyl), carbonyl (-C(=O)-R, wherein R is C1-C10 alkyl or alkenyl), carboxyl (-COOH), and any combination thereof.

[0030] As used herein, the term "organic group" refers to a linear or branched C1-C30 alkyl, a linear or branched C2-C30 alkenyl, or a linear or branched C2-C30 alkynyl. In addition, the alkyl, alkenyl, and alkynyl may be substituted or unsubstituted.

[0031] As used herein, the term "alkyl" refers to a monovalent substituent derived from a linear or branched saturated hydrocarbon having 1 to 40 carbon atoms. Examples thereof may include methyl, ethyl, propyl, isobutyl, sec-butyl, pentyl, isopentyl, hexyl, etc., but are not limited thereto. As used herein, the term "alkylene" refers to a divalent group having the same structure as an alkyl derived from a linear or branched saturated hydrocarbon having 1 to 40 carbon atoms.

[0032] As used herein, the term "alkenyl" refers to a monovalent substituent derived from a linear or branched unsaturated hydrocarbon having 2-40 carbon atoms and at least one carbon-carbon double bond. Examples thereof may include vinyl, allyl, isopropenyl, 2-butenyl, etc., but are not limited thereto. As used herein, the term "alkenylene" refers to a divalent group having the same structure as an alkenyl derived from a linear or branched unsaturated hydrocarbon having at least one carbon-carbon double bond and 2-40 carbon atoms.

[0033] <Quantum dot composition>

[0034] The quantum dot composition according to an embodiment of the present disclosure may include quantum dots, a photopolymerizable monomer, and an oligomer. The oligomer may include a compound including a carbon-carbon double bond and a compound including a thiol group.

[0035] The quantum dot composition according to an embodiment of the present disclosure may be used for electrohydrodynamic inkjet printing, and may have a viscosity of 5000 cp or less, such as about 100 cp to about 1000 cp, such as about 150 cp to about 600 cp.

[0036] Hereinafter, the chemical composition of the quantum dot composition will be described below.

[0037] quantum dots

[0038] Quantum dots (QDs), which are nanometer-sized semiconductor materials, may have various energy band gaps depending on size and composition, and accordingly emit light having various wavelengths.

[0039] The quantum dots may have a uniform single layer structure; a multilayer structure such as a core-shell structure and a gradient structure; or any hybrid structure thereof. In the core-shell structure, the shell may have multiple layers (e.g., core / shell / shell), wherein each layer may include a different component, e.g., a metal (metalloid) oxide.

[0040] Quantum dots (QDs) can be freely selected from II-VI compounds, III-V compounds, IV-VI compounds, IV elements (simple substances), IV compounds, and any combination thereof. When the quantum dots have a core-shell structure, the core and the shell can be freely formed by the components exemplarily described below.

[0041] For example, the II-VI group compound can be selected from: a binary compound selected from the following: CdO, CdS, CdSe, CdTe, ZnO, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, MgSe, MgS, and any mixture thereof; a ternary compound selected from the following: CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, and any mixture thereof; and a quaternary compound selected from the following: CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, and any mixture thereof.

[0042] As another example, the III-V compound may be selected from: a binary compound selected from the following: GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, and any mixture thereof; a ternary compound selected from the following: GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, and any mixture thereof; and a quaternary compound selected from the following: GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, and any mixture thereof.

[0043] As another example, the IV-VI group compound can be selected from: a binary compound selected from the following: SnS, SnSe, SnTe, PbS, PbSe, PbTe, and any mixture thereof; a ternary compound selected from the following: SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, and any mixture thereof; and a quaternary compound selected from the following: SnPbSSe, SnPbSeTe, SnPbSTe, and any mixture thereof.

[0044] As another example, the Group IV element may be selected from Si, Ge, and any mixture thereof. The Group IV compound may be selected from: a binary compound selected from SiC, SiGe, and any mixture thereof.

[0045] As another example, as an alloy type compound, the Group IV compound may be a ternary compound selected from InZnP and the like.

[0046] The above binary, ternary, or quaternary compounds can be present in the particles in uniform concentrations or in the same particles with partially different concentration distributions. In addition, the compound can have a core-shell structure in which one quantum dot surrounds another quantum dot. The interface between the core and the shell can have a concentration gradient in which the concentration of the element present in the shell decreases toward the center.

[0047] The shape of the quantum dot is not particularly limited as long as the shape is commonly used in the art. For example, the shape of the quantum dot can be spherical, rod-shaped, pyramidal, disc-shaped, multi-armed, or cubic nanoparticles, nanotubes, nanowires, nanofibers, and nanosheet particles.

[0048] In addition, the size of the quantum dot is not particularly limited and can be adjusted within the range generally known in the art. For example, the quantum dot may have an average particle size (particle diameter) D50 of about 2 nanometers (nm) to about 10nm. By adjusting the particle size of the quantum dot to a range of about 2nm to about 10nm, light with a desired color can be emitted. For example, when the particle size of the quantum dot core / shell including InP is about 5nm to about 6nm, light with a wavelength of about 520nm to about 550nm can be emitted. At the same time, when the particle size of the quantum dot core / shell including InP is about 7nm to about 8nm, light with a wavelength of about 620nm to about 640nm can be emitted. For example, as a QD emitting blue, a non-cadmium (Cd)-based III-V compound QD (e.g., InP, InGaP, InZnP, GaN, GaAs, and GaP) can be used.

[0049] In addition, the quantum dots may have a half width (FWHM) of about 40 nm or less in the light emission wavelength spectrum. Within the range of the half width, color purity or color reproducibility may be improved. In addition, the light emitted from the quantum dots travels in all directions, and thus the optical viewing angle may be widened.

[0050] According to an embodiment of the present disclosure, depending on the properties of the quantum dots, the amount of the quantum dots may be from about 1 weight percent (wt %) to about 60 wt %, for example, from about 20 wt % to about 60 wt %, based on the total weight of the quantum dot composition.

[0051] Oligomer

[0052] In the quantum dot composition according to the present disclosure, the oligomer may include a compound comprising a carbon-carbon double bond and a compound comprising a thiol group. For example, the oligomer may include two or more types of compounds comprising a carbon-carbon double bond, for example, a compound comprising two or three carbon-carbon double bonds per molecule and a compound comprising one carbon-carbon double bond per molecule.

[0053] In the case of containing two or three carbon-carbon double bonds per molecule, the oligomer may have a molecular weight of about 200 g / mol to about 1000 g / mol, such as about 200 grams / mole (g / mol) to about 800 g / mol, such as about 200 g / mol to about 500 g / mol. For example, triallyl isocyanurate and the like may be used.

[0054] In this regard, the compound containing a carbon-carbon double bond may include one or more types of compounds containing a phenol group, for example, the compound containing a phenol group may be a compound containing one carbon-carbon double bond per molecule. In the post-treatment after the quantum dot composition is cured, the ligand on the surface of the quantum dot can be discharged in the form of a gas (hereinafter referred to as exhaust) to cause product defects such as cracks and poor lamination in the cured film, light-emitting element, and display device. When one or more compounds containing a phenol group are used, the generation of exhaust can be reduced. For example, phenol acrylates, etc. can be used.

[0055] The compound containing a thiol group may include 2-4 functional groups, for example, 2-4 thiol groups per molecule, for example, 2 or 3 thiol groups per molecule. For example, ethylene glycol di(3-mercaptopropionate) and the like may be used. Suitable functional groups include esters (-C(=O)O-), ethers (-O-), carbonyls (-C(=O)-), carboxyls (-C(=O)-OH), sulfonyls (-SO 2 -), thioether (sulfide) (-S-), sulfoxide (-SO-), alkoxy (C n H 2n+1 O-, n is an integer from 1 to 20), and hydroxyl group (-OH).

[0056] The molar ratio of the compound comprising a carbon-carbon double bond to the compound comprising a thiol group may be about 2.75:1 to about 5:1, for example about 2.75:1 to about 4:1, for example about 2.75:1 to about 3.5:1.

[0057] Additionally, the molar ratio of the compound containing two or three carbon-carbon double bonds per molecule to the compound containing one carbon-carbon double bond per molecule may be from about 0.01:1 to about 1.5:1, such as from about 0.1:1 to about 1.5:1, such as from about 0.3:1 to about 1.2:1.

[0058] In the compound containing a carbon-carbon double bond, the carbon-carbon double bonds may each independently be included in at least one group selected from the group consisting of an allyl group, a vinyl group, a (meth)acryloyl group, an isopropenyl group, or a 2-butenyl group, but is not limited thereto.

[0059] According to an embodiment of the present disclosure, depending on the properties of the quantum dots, the amount of the oligomer may be from about 1 wt % to about 50 wt %, such as from about 10 wt % to about 45 wt %, such as from about 10 wt % to about 30 wt %, based on the total weight of the quantum dot composition.

[0060] Ligand

[0061] In the quantum dot composition according to the present disclosure, the ligand is used to modify the surface of the quantum dots. Due to the hydrophobic surface properties, the quantum dots have obstacles to dispersion in the photopolymerizable monomer. The miscibility of the quantum dots with the photopolymerizable monomer can be improved by modifying the surface of the quantum dots with appropriate ligands.

[0062] According to an embodiment of the present disclosure, the ligand may include a first ligand represented by the following Formula 1 and a second ligand including 3 to 40 (preferably, 3 to 16) carbon atoms and having a carboxyl group.

[0063] [Formula 1]

[0064]

[0065] In Formula 1, M is a divalent to tetravalent metal, m is an integer of 1-4, each X is independently a C3-C20 organic group, and n is an integer of 2-4.

[0066] The first ligand may be a metal-thiol-based compound formed through a reaction between a metal salt and a thiol-based compound.

[0067] In the first ligand, M is a divalent to tetravalent metal. For example, as a metal of Group II-IV, M may be Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Cd, In, or Sn. In Formula 1, n is determined by the valence of M and is an integer of 2-4.

[0068] In addition, in Formula 1, X may independently be a C3-C20 organic group. For example, X may be a C3-C20 alkylene or alkenylene group containing at least one functional group selected from the group consisting of an ester group (—C(═O)—), an ether group (—O—), a carbonyl group (—C(═O)—), a carboxyl group (—C(═O)—OH), a sulfonyl group (—SO 2 -), sulfide (-S-), sulfoxide (-SO-), alkoxy (C n H 2n+1 O-, n is an integer from 1 to 20), cycloalkyl (-C n H 2n-1 , n is an integer from 1 to 20), or a hydroxyl group (—OH). For example, X may be a C4-C20 organic group including an ester group (—C(═O)O—).

[0069] In the first ligand, the thiol group having excellent affinity with the surface of each quantum dot can improve the dispersibility of the quantum dot in the photopolymerizable monomer. In addition, since the first ligand includes not only a thiol group, but also an ester group, an ether group, a carbonyl group, a carboxyl group, an alkoxy group, a cycloalkyl group, or a hydroxyl group, the dispersibility of the surface-modified quantum dots in the hydrophobic polar monomer can be increased. In addition, the quantum dot composition including such quantum dots can have properties that are conducive to the electrohydrodynamic (EHD) inkjet method. At the same time, in the case of using a thiol-based compound with three or less carbon atoms, the surface of each quantum dot can be modified, but due to the high polarity of the surface-modified quantum dots, the dispersibility in common solvents and monomers can be reduced.

[0070] The second ligand may include 3-40 carbon atoms and a carboxyl group. In addition, according to an embodiment of the present disclosure, the second ligand may not include a thiol group.

[0071] According to an embodiment of the present disclosure, the second ligand may be represented by Formula 2 below.

[0072] [Formula 2]

[0073]

[0074] In Formula 2, L is a single bond or selected from substituted or unsubstituted C1-C20 alkylene and substituted or unsubstituted C2-C20 alkenylene, A is a single bond or a C1-C20 alkylene or alkenylene containing a functional group selected from the following: ester group (-C(=O)O-), ether group (-O-), carbonyl group (-C(=O)-), sulfonyl group (-SO 2 -), thioether group (-S-), and sulfoxide group (-SO-), and R is hydrogen or selected from substituted or unsubstituted C1-C20 alkyl group and substituted or unsubstituted C2-C20 alkenyl group.

[0075] For example, in the second ligand, A may include an ester group (-COO-), an ether group (-O-), or any combination thereof. In addition, A may be a C2-C15 alkylene or alkenylene group, for example, a C2-C10 alkylene or alkenylene group.

[0076] Generally, thiol-based ligands are known to have high reactivity with the surface of the quantum dot. However, due to problems such as harmful, small or poor storage stability, quantum dot compositions containing only thiol-based ligands may not be suitable for compositions for inkjet printing. Due to the use of the first ligand containing a thiol-based ligand and due to the use of the second ligand not containing a thiol-based ligand, the quantum dot composition according to the present disclosure may have excellent storage stability. In addition, due to the inclusion of functional groups such as ester groups (-C(=O)O-), ether groups (-O-), carbonyl groups (-C(=O)-), and carboxyl groups (-C(=O)-OH), the second ligand may have excellent dispersibility in photopolymerizable monomers. At the same time, when the number of carbon atoms of the second ligand is greater than 16, surface modification of the quantum dot may not occur, or the dispersibility in common solvents or monomers may deteriorate.

[0077] According to an embodiment of the present disclosure, the molar ratio of the first ligand to the second ligand may be about 1:30 to about 20:1, such as about 1:15 to about 10:1, such as about 1:8 to about 5:1, but is not limited thereto.

[0078] In addition, according to an embodiment of the present disclosure, the mixing weight ratio of the quantum dots to the ligands may be about 1:1 to about 1:20, for example, about 1:1 to about 1:10, for example, about 1:5 to about 1:10. In this regard, the ligand refers to the sum of the first ligand and the second ligand.

[0079] Photopolymerizable monomers

[0080] In the quantum dot composition according to the present disclosure, the photopolymerizable monomer can control the overall crosslinking density of the formulation (i.e., polymer matrix) in which the quantum dots (QDs) are dispersed to express the structure and overall physical properties of the matrix. In addition, flexibility and adhesion to other materials can also be improved.

[0081] The photopolymerizable monomer may include an aromatic monomer containing an aromatic ring such as a phenoxy group, a phenol group or a phenyl group. For example, the aromatic monomer may be one selected from the following: phenoxyethyl acrylate, phenoxyethyl methacrylate, o-phenylphenoxyethyl acrylate, phenoxybenzyl acrylate, benzyl acrylate, benzyl methacrylate, biphenyl methyl acrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol A ethoxylate dimethacrylate, bisphenol A ethoxylate diacrylate, bisphenol A glycerol diacrylate, bisphenol F ethoxylate diacrylate, or any combination thereof. The photopolymerizable monomer may include one or more types of aromatic monomers. Due to the high refractive index of 1.50 or more, the aromatic monomer can achieve the effect of improving light conversion efficiency.

[0082] In the present disclosure, according to the quantum dots, the amount of the aromatic monomer may be about 1 wt % to about 20 wt %, for example about 3 wt % to about 15 wt %, based on the total weight of the quantum dot composition.

[0083] In addition, the photopolymerizable monomer may include a monomer based on (meth) acrylate. For example, the monomer based on (meth) acrylate may include at least one selected from (meth) acryloyl, vinyl, or allyl. For example, 1,6-hexanediol diacrylate, 1,6-cyclohexanediol diacrylate, 2,2-dimethyl-1,3-propanediol diacrylate, diethylene glycol diacrylate, dipropylene glycol diacrylate, 1,3-butylene glycol dimethacrylate, trimethylolpropane trimethacrylate, isobornyl acrylate, isobornyl methacrylate, tetrahydrofuran acrylate, acryloyl morpholine, 2-phenoxyethyl acrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol mono(meth) acrylate, pentaerythritol di(meth) acrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, dipentaerythritol hexaacrylate, dipentaerythritol hexamethacrylate, etc. can be used. These compounds may be used alone or in a mixture of two or more thereof. In the present disclosure, as a (meth)acrylate-based monomer, 1,6-hexanediol diacrylate may be suitable for obtaining the viscosity property of the quantum dot composition.

[0084] In the present disclosure, according to the quantum dots, the amount of the photopolymerizable monomer may be about 1 wt % to about 60 wt %, for example about 3 wt % to about 50 wt %, based on the total weight of the quantum dot composition.

[0085] Photoinitiator

[0086] In the quantum dot composition according to the present disclosure, the photoinitiator is a component excited by a light source such as ultraviolet (UV) rays to initiate photopolymerization, and any photopolymerization photoinitiator generally available in the art can be used. For example, acetophenone-based compounds, benzophenone-based compounds, thioxanthone-based compounds, benzoin-based compounds, triazine-based compounds, and oxime-based compounds can be used.

[0087] Non-limiting examples of the photoinitiator may include ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate, Irgacure 184, Irgacure 369, Irgacure 651, Irgacure 819, Irgacure 907, benzoin alkyl ether, benzophenone, benzil dimethyl ketal, hydroxycyclohexyl phenyl acetone, chloroacetophenone, 1,1-dichloroacetophenone, diethoxyacetophenone, hydroxyacetophenone, 2-chlorothioxanthone, 2-ethylanthraquinone (2-ETAQ), 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, or methyl benzoylformate. These compounds may be used alone or in combination of two or more thereof.

[0088] The amount of the photoinitiator can be appropriately adjusted within a range known in the art. For example, based on the total weight of the quantum dot composition, the amount of the photoinitiator can be about 0.01 wt % to about 10 wt %, such as about 0.1 wt % to about 5 wt %. Within the range of the amount of the photoinitiator, photopolymerization can be fully performed without deterioration of the physical properties of the substrate.

[0089] Diffuser

[0090] In the quantum dot composition according to the present disclosure, the diffusing agent reflects light not absorbed by the photoconversion material and allows the photoconversion material to absorb the reflected light again. That is, the diffusing agent can increase the photoconversion efficiency by increasing the amount of light absorbed by the photoconversion material.

[0091] The diffusing agent may be any diffusing agent known in the art without limitation. The diffusing agent may be a solid or a dispersion in which the diffusing agent is dispersed.

[0092] Non-limiting examples of the diffusing agent used herein may include barium sulfate (BaSO 4 ), calcium carbonate (CaCO 3 ), titanium dioxide (TiO 2 ), zirconium oxide (ZrO 2), or any combination thereof. In addition, the average particle size or shape of the diffusing agent is not particularly limited and can be selected from configurations known in the art. For example, the average particle size (D50) can be about 150 nm to about 250 nm, such as about 180 nm to about 230 nm. When the average particle size of the diffusing agent is within the above range, the light diffusion effect can be improved and the light conversion efficiency can be increased.

[0093] The amount of the diffusing agent can be appropriately adjusted within a range known in the art. For example, based on the total weight of the quantum dot composition, the amount of the diffusing agent can be about 0.01 wt % to about 10 wt %, such as about 0.1 wt % to about 5 wt %. Within the range of the amount of the diffusing agent, the effect of improving the light conversion efficiency can be obtained without deterioration of the physical properties of the substrate.

[0094] Polymerization inhibitors

[0095] In the quantum dot composition according to the present disclosure, the polymerization inhibitor, as a material that forms low-reactive radicals or compounds that cannot participate in polymerization with radicals, can adjust the reaction rate of photopolymerization.

[0096] The polymerization inhibitor may be any material known in the art without limitation. For example, the polymerization inhibitor may be a quinone-based compound, a phenol- or aniline-based compound, an aromatic nitro- and nitroso-based compound. For example, hydroquinone (HQ), methyl hydroquinone (THQ), hydroquinone monomethyl ether (MEHQ) and hydroquinone monoethyl ether (EEHQ), 1,4-benzoquinone (BQ), 2,5-diphenylbenzoquinone (DPBQ), methyl-1,4-benzoquinone (MBQ), phenyl-1,4-benzoquinone (PBQ); 2,6-di-tert-butyl-4-methylphenol (BHT), 2,6-diphenyl-4-octadecyloxyphenol, catechol; phenothiazine, bis(α-methylbenzyl)phenothiazine, 3,7-dioctylphenothiazine, bis(α,α-dimethylbenzyl)phenothiazine; dimethyldithiocarbamic acid, diethyldithiocarbamic acid, dipropyldithiocarbamic acid, dibutyldithiocarbamic acid, diphenyldithiocarbamic acid, etc. can be used. These compounds can be used alone or in combination of two or more thereof.

[0097] The amount of the polymerization inhibitor may be appropriately adjusted within a range known in the art. For example, based on the total weight of the quantum dot composition, the amount of the polymerization inhibitor may be about 0.01 wt % to about 2 wt %, such as about 0.05 wt % to about 1 wt %.

[0098] Other additives

[0099] In addition to the above components, the quantum dot composition of the present disclosure may further include any additive known in the art without limitation within the range not impairing the effects of the present disclosure. The amount of the additive may be appropriately adjusted within the range known in the art.

[0100] Examples of usable additives may include silane-based compounds, siloxane-based compounds, antioxidants, leveling agents, lubricants, surface conditioners, surfactants, adhesion promoters, defoamers, slip agents, solvents, humectants, light stabilizers, antifouling agents, softeners, thickeners, and polymers. These additives may be used alone or in combination of two or more thereof.

[0101] The silane-based compound is used to provide adhesion to a substrate, and the siloxane-based compound is used to provide wetting properties. The silane-based compound and the siloxane-based compound may be any components known in the art without limitation.

[0102] The antioxidant is used to inhibit the fading caused by heat or light, and to prevent the fading caused by various oxidizing gases such as ozone, active oxygen, NOx, and SOx (wherein X is an integer). In the present disclosure, by adding the antioxidant, the coloring of the substrate can be inhibited or the reduction of the film thickness caused by decomposition can be reduced. The example of the antioxidant can include hydrazides, hindered amine type antioxidants, nitrogen-containing heterocyclic thiol compounds, thioether-based antioxidants, hindered phenol-based antioxidants, ascorbic acid, zinc sulfate, thiocyanates, thiourea derivatives, sugars, nitrites, sulfites, thiosulfates, and hydroxylamine derivatives.

[0103] The leveling agent may be included for the following purpose: improving adhesion in the composition by leveling the quantum dot composition so that the quantum dot composition is applied as a flat and smooth film. As the leveling agent, acrylic compounds, silicone compounds, etc. may be used alone or as a mixture of two or more thereof. For example, the leveling agent may include polyether-modified polydimethylsiloxane, and may have a structure in which a (meth)acryloyl group is located in a polyether chain.

[0104] The surfactant may be included for the miscibility and coating uniformity of the quantum dot composition. The surfactant may be a cationic, anionic, zwitterionic, and nonionic surfactant well known in the art. For example, at least one of a fluorine-based surfactant, a silicone-based surfactant, or a fluorine-silicone-based surfactant may be used.

[0105] The light stabilizer, as a UV absorber, has the effect of improving the weather resistance of the matrix. The softener is used to reduce the occurrence of cracks in the dried polymer matrix and can improve the impact resistance and bending resistance by reducing the occurrence of cracks in the cured matrix.

[0106] <Method for producing quantum dot composition>

[0107] Reference Figure 1 , a method 100 for manufacturing a quantum dot composition according to an embodiment of the present disclosure may include: modifying the surface of quantum dots (frame 101) and dispersing the quantum dots in a photopolymerizable monomer to obtain a quantum dot dispersion (frame 102), and additionally adding an oligomer and a photopolymerizable monomer to the quantum dot dispersion (frame 103), wherein the additionally added photopolymerizable monomer includes an aromatic monomer having an aromatic ring such as a phenoxy group, a phenol group, or a phenyl group.

[0108] The oligomer may include a compound including a carbon-carbon double bond and a compound including a thiol group, and the oligomer may be prepared by stirring and polymerizing at room temperature before being mixed with the quantum dot dispersion. The oligomer may further include a photoinitiator and a polymerization inhibitor.

[0109] Modifying the surface of the quantum dots of block 101 may include primary surface modification by adding a first ligand represented by the following Formula 1 (block 1011 ), and secondary surface modification by adding a second ligand including 3 to 40 carbon atoms and having a carboxyl group (block 1012 ).

[0110] [Formula 1]

[0111]

[0112] In Formula 1, M is a divalent to tetravalent metal, m is an integer of 1-4, each X is independently a C3-C20 organic group, and n is an integer of 2 to 4.

[0113] For example, after synthesizing the quantum dots, the first ligand is added to the solution containing the synthesized quantum dots to perform a primary surface modification, followed by centrifugation to obtain the primary surface-modified quantum dots. Then, the primary surface-modified quantum dots are dispersed in the photopolymerizable monomer, and a second ligand including 3-40 carbon atoms and having a carboxyl group is added to perform a secondary surface modification.

[0114] In this regard, the method of manufacturing quantum dots may be performed by using any method disclosed in numerous literatures (eg, a high temperature injection method, a method using a microfluidic reactor, and microwave irradiation).

[0115] Each of the quantum dots can be modified once by adding the first ligand to a solution containing the synthesized quantum dots and maintained at about 60° C. and stirring the mixture for about 30 minutes to about 3 hours, and then modified twice by adding the second ligand thereto and stirring the mixture for about 30 minutes to about 3 hours.

[0116] By performing the surface modification of each quantum dot in two steps, the formation of an adduct resulting from the reaction between the first ligand and the second ligand can be prevented. In contrast, in the case of adding the first ligand and the second ligand to each quantum dot simultaneously (block 1013), an adduct can be formed by a thiol-ene reaction between the thiol group of the first ligand and the acrylate of the second ligand.

[0117] After modifying the surface of each quantum dot as described above, the surface-modified quantum dot can be obtained by centrifugation. In addition, a quantum dot dispersion can also be prepared by dispersing the obtained surface-modified quantum dot in the photopolymerizable monomer.

[0118] Subsequently, the photopolymerizable monomer may be further added to the prepared quantum dot dispersion and oligomer, and the polymerization inhibitor, the photoinitiator, and the diffusing agent may be further mixed therewith to prepare a quantum dot composition. In this regard, the additionally added photopolymerizable monomer may include at least one type of aromatic monomer having an aromatic ring such as a phenoxy group, a phenol group, or a phenyl group, and the amount of the aromatic monomer may be about 1 wt % to about 20 wt %, such as about 3 wt % to about 15 wt %, based on the total weight of the quantum dot composition.

[0119] Additionally, the photopolymerizable monomer is as described above in the quantum dot composition in the repeating range.

[0120] <Cured product, light-emitting element, and display device>

[0121] refer to Figure 2 The present disclosure may provide a cured product including the above-mentioned quantum dot composition. The cured product according to the present disclosure may have excellent optical properties, for example, 80% or more light absorption. In addition, the cured product may have a light conversion rate of 35% or more.

[0122] The cured product may be prepared by: forming a pattern by applying the above-mentioned quantum dot composition to a base material (substrate) through spin coating; and curing the pattern.

[0123] The present disclosure provides a light emitting element 201 including the above quantum dot composition. For example, a color filter is an optical component in the form of a thin film that extracts red, green, and blue light on a pixel basis from white light emitted from a rear (back) light source and realizes color in a liquid crystal display.

[0124] The color filter can be manufactured by dyeing, pigment dispersion, printing, electrodeposition, etc. In addition, the color filter including the quantum dot composition can be manufactured by inkjet printing. The inkjet printing can avoid unnecessary waste of materials because the materials are only used in the desired pixels.

[0125] The present disclosure also provides a display device 202 including the above quantum dot composition. In this regard, the display device may be a liquid crystal display (LCD) device, an electroluminescent (EL) display device, a plasma display device (PDP), a field emission display (FED) device, an organic light emitting element (OLED), etc., but is not limited thereto.

[0126] Hereinafter, the present disclosure will be described in more detail with reference to the following examples. However, the following examples are only presented to illustrate the present disclosure, and the scope of the present disclosure is not limited thereto.

[0127] [Preparation Example 1] Preparation of the First Ligand

[0128] 1) About 280 g of poly(ethylene glycol) methyl ether 400 and about 50 g of mercaptosuccinic acid were reacted at about 100° C. for about 12 hours. After the reaction was completed, the resultant was cooled to room temperature to obtain 330 g of bis(methoxypolyethylene glycol) mercaptosuccinate-400.

[0129] 2) Add 1.7 g zinc chloride (ZnCl) to 134.5 g hexyl acetate in a round bottom flask. 2 ) and 32 g of bis(methoxypolyethylene glycol) mercaptosuccinate-400, and dissolved by stirring at about 60° C. Then, HCl was removed under vacuum for 2 hours to prepare a first ligand, i.e., Zn-bis(methoxypolyethylene glycol) mercaptosuccinate-400.

[0130] [Preparation Example 2] Preparation of the Second Ligand

[0131] The compound represented by Formula B-1 was added to hexyl acetate in a round-bottom flask and stirred at room temperature for about 1 hour to prepare a second ligand, ie, mono(2-acryloyloxyethyl)succinate.

[0132] [B-1]

[0133]

[0134] [Preparation Example 3] Preparation of Quantum Dot (QD) Dispersion

[0135] 1) 750 ml of InZnP / ZnSe / ZnS (core / shell / shell) quantum dot dispersion solution (Hansol, 20 wt% quantum dot solid content; hexyl acetate) was heated to about 60° C. in a nitrogen atmosphere while stirring. About 9 g of Zn-bis(methoxypolyethylene glycol)mercaptosuccinate-400 as the prepared first ligand was added thereto, followed by stirring to perform primary surface modification on the quantum dots.

[0136] 2) About 30 g of mono(2-acryloyloxyethyl)succinate as the prepared second ligand was added to the solution including the primary surface-modified quantum dots, followed by stirring for about 2 hours to perform secondary surface modification.

[0137] 3) The solution including the surface-modified quantum dots was centrifuged twice with cyclohexane to obtain a quantum dot powder, and the powder was dispersed in 1,6-hexanediol diacrylate (MIWON) at a concentration of 60 wt % to prepare a QD dispersion.

[0138] [Preparation Example 4] Preparation of oligomer A

[0139] 1 part by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) and 0.1 part by weight of methylhydroquinone were dissolved in 100 parts by weight of triallyl isocyanurate to prepare a crude solution A. 42.9 parts by weight of the crude solution A, 28.6 parts by weight of phenol acrylate and 28.6 parts by weight of ethylene glycol di(3-mercaptopropionate) were mixed and stirred at room temperature for 1 hour. After stirring, the temperature of the reactor was set to about 80°C to prepare oligomer A by oligomer polymerization.

[0140] <Example 1-1> Preparation of quantum dot composition

[0141] After mixing 70 parts by weight of a surface-modified green quantum dot dispersion (Hansol, 60 parts by weight of quantum dot polymer: 40 parts by weight of 1,6-hexanediol diacrylate) with 14.5 parts by weight of oligomer A, the mixture was mixed with 5.4 parts by weight of 1,6-hexanediol diacrylate (MIWON), 3 parts by weight of phenoxyethyl acrylate (GreenChemical), 0.1 parts by weight of methylhydroquinone, 2 parts by weight of ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate as a photoinitiator, and 5 parts by weight of titanium dioxide as a diffuser to prepare a quantum dot composition.

[0142] <Example 1-2>

[0143] A quantum dot composition was prepared in the same manner as in Example 1-1, except that 12.5 parts by weight of oligomer A and 5 parts by weight of phenoxyethyl acrylate were used.

[0144] <Examples 1-3>

[0145] A quantum dot composition was prepared in the same manner as in Example 1-1, except that 10.5 parts by weight of oligomer A and 7 parts by weight of phenoxyethyl acrylate were used.

[0146] <Examples 1-4>

[0147] A quantum dot composition was prepared in the same manner as in Example 1-1, except that 3 parts by weight of bisphenol A diacrylate was used instead of 3 parts by weight of phenoxyethyl acrylate.

[0148] <Examples 1-5>

[0149] A quantum dot composition was prepared in the same manner as in Example 1-2, except that 5 parts by weight of bisphenol A diacrylate was used instead of 5 parts by weight of phenoxyethyl acrylate.

[0150] <Comparative Example 1-1>

[0151] A quantum dot composition was prepared in the same manner as in Example 1-1, except that 17.5 parts by weight of oligomer A was used instead of 14.5 parts by weight of oligomer A and 3 parts by weight of phenoxyethyl acrylate.

[0152] <Comparative Example 1-2>

[0153] A quantum dot composition was prepared in the same manner as in Comparative Example 1-1, except that 10.5 parts by weight of oligomer A was used and 12.4 parts by weight of 1,6-hexanediol diacrylate was used.

[0154] <Comparative Examples 1-3>

[0155] A quantum dot composition was prepared in the same manner as in Comparative Example 1-1, except that 22.9 parts by weight of 1,6-hexanediol diacrylate was used instead of 17.5 parts by weight of oligomer A and 5.4 parts by weight of 1,6-hexanediol diacrylate.

[0156] <Example 2-1>

[0157] After mixing 46.5 parts by weight of a surface-modified red quantum dot composition (Hansol, 60% by weight of quantum dot polymer: 40% by weight of 1,6-hexanediol diacrylate) with 35.5 parts by weight of oligomer A, the mixture was mixed with 5.9 parts by weight of 1,6-hexanediol diacrylate, 5 parts by weight of bisphenol A diacrylate, 0.1 parts by weight of methylhydroquinone, 2 parts by weight of ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate as a photoinitiator, and 5 parts by weight of titanium dioxide as a light scattering agent to prepare a quantum dot composition.

[0158] <Comparative Example 2-1>

[0159] A quantum dot composition was prepared in the same manner as in Example 2-1, except that 10.9 parts by weight of 1,6-hexanediol diacrylate was used instead of 5.9 parts by weight of 1,6-hexanediol diacrylate and 5 parts by weight of bisphenol A diacrylate.

[0160] <Comparative Example 2-2>

[0161] A quantum dot composition was prepared in the same manner as in Comparative Example 2-1, except that 46.4 parts by weight of 1,6-hexanediol diacrylate was used instead of 35.5 parts by weight of oligomer A and 10.9 parts by weight of 1,6-hexanediol diacrylate.

[0162] The compositions of the Examples and Comparative Examples are shown in Tables 1A, 1B and 1C below.

[0163] Table 1A

[0164]

[0165] Table 1B

[0166]

[0167]

[0168] Table 1C

[0169]

[0170] Experimental Example 1. Evaluation of light conversion efficiency and light absorption of the cured product of quantum dots

[0171] 1) The green quantum dot compositions of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 were applied to a 2 cm x 2 cm glass substrate to a thickness of 10 μm by using a spin coater (Mikasa, Opticoat MS-A150), and cured by using an LED curing device with a wavelength of 395 nm at 4000 mJ / cm 2 Curing to prepare a cured film. Subsequently, a single film sample with a size of 2 cm x 2 cm was loaded in an integrating sphere device (QE-2100, Otsuka electronics) to measure the initial light absorption and the light conversion efficiency (QE) after curing. Then, the resultant was heat treated (post-baking) at 180 ° C for 30 minutes in a nitrogen atmosphere, and its light conversion efficiency (QE) was measured. The results are shown in Tables 2A and 2B below.

[0172] Table 2A

[0173]

[0174]

[0175] Table 2B

[0176] Photoconversion efficiency (after curing + heat treatment) (%) Wavelength (nm) FWHM(nm) Example 1-1 34.3 533.4 35.8 Example 1-2 34.6 533.4 36.0 Examples 1-3 35.0 533.5 36.2 Examples 1-4 35.0 533.5 35.8 Examples 1-5 35.3 533.6 35.9 Comparative Example 1-1 33.8 533.6 35.9 Comparative Example 1-2 32.5 533.6 36.0 Comparative Examples 1-3 31.8 533.5 35.8

[0177] The cured films according to Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 were prepared in a uniform thickness ranging from about 0.3 μm to about 10 μm.

[0178] All of Examples 1-1 to 1-5 exhibited light absorption of not less than 85% and light conversion efficiency of not less than 34%, indicating excellent optical properties.

[0179] For example, as the amount of phenoxyethyl acrylate increases, the light conversion rate increases from 34.3% to 35.0% in Examples 1-1 to 1-3. As the amount of bisphenol A diacrylate increases, the light conversion rate increases from 35.0% to 35.3% in Examples 1-4 to 1-5. On the contrary, in Comparative Examples 1-1 to 1-3 in which the quantum dot composition does not include an aromatic monomer having an aromatic ring such as a phenoxy group, a phenol group, or a phenyl group, the light absorption is not less than 85%, but the light conversion rate ranges from 31.8% to 33.8%, indicating a relatively low level.

[0180] Therefore, since the excellent optical properties are maintained before and after heat treatment according to Examples 1-1 to 1-5, the light-emitting element or display device including the quantum dot composition of Examples 1-1 to 1-5 can have excellent optical properties maintained for a longer period of time compared to the light-emitting element or display device including the quantum dot composition of Comparative Examples 1-1 to 1-3.

[0181] 2) After preparing a cured film using the red quantum dot composition prepared in Example 2-1 and Comparative Examples 2-1 and 2-2 in the same manner as above, the light absorption and light conversion efficiency were measured. Moreover, after heat treatment in the same manner as above, the light conversion efficiency was measured. The results are shown in Tables 3A and 3B below.

[0182] Table 3A

[0183] Thickness(μm) Light absorption (%) Photoconversion rate (after curing) (%) Example 2-1 10.1 88.1 40.5 Comparative Example 2-1 9.9 87.8 39.2 Comparative Example 2-2 10.0 88.9 35.8

[0184] Table 3B

[0185] Photoconversion efficiency (after curing + heat treatment) (%) Wavelength (nm) FWHM(nm) Example 2-1 41.4 645.6 38.2 Comparative Example 2-1 40.1 645.7 38.0 Comparative Example 2-2 36.6 645.6 38.1

[0186] All light absorption was from about 88% to about 89%. While the light conversion rate of Example 2-1 was 41.4%, the light conversion rate of Comparative Example 2-1, which did not include bisphenol A diacrylate as an aromatic monomer, was slightly reduced to 40.1%, and a lower light conversion rate of 36.6% was observed in Comparative Example 2-2, which did not include either bisphenol A diacrylate or an oligomer.

[0187] Therefore, since the excellent optical properties are maintained before and after heat treatment according to Example 2-1, the light-emitting element or display device including the quantum dot composition of Example 2-1 can have excellent optical properties maintained for a longer period of time compared to the light-emitting element or display device including the quantum dot compositions of Comparative Examples 2-1 and 2-2.

[0188] Experimental Example 2. Evaluation of Viscosity of Quantum Dot Composition

[0189] The viscosity of the green quantum dot compositions according to Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 was measured. In this regard, the viscosity was measured at room temperature (25° C.) by using a rheometer (Thermo Scientific, HAAKE MARS).

[0190] Furthermore, the viscosity of the red quantum dot compositions of Example 2-1 and Comparative Examples 2-1 and 2-2 was measured in the same manner. The results are shown in Tables 4A and 4B below.

[0191] Table 4A

[0192]

[0193] Table 4B

[0194] Example 2-1 Comparative Example 2-1 Comparative Example 2-2 Viscosity (cp, 25℃) 582 552 26

[0195] The green quantum dot composition according to the embodiment exhibited a viscosity of about 151 cp to about 289 cp, and the red quantum dot composition according to the embodiment exhibited a viscosity of about 582 cp, indicating a suitable viscosity for EHD inkjet printing.

[0196] In contrast, the quantum dot compositions of Comparative Examples 1-3 and 2-2, which do not include the oligomer, exhibited low viscosities of about 35 cp and 26 cp, indicating that they are not suitable for EHD inkjet printing.

[0197] In addition, although Comparative Examples 1-1 and 2-1 not including the aromatic monomer are suitable in terms of viscosity, considering the results of Experimental Examples 1 and 2, there may be difficulties in practical application.

[0198] Experimental Example 3. Evaluation of electrohydrodynamic (EHD) inkjet printing (ink ejection capability)

[0199] The ink jetting ability (jetting performance) of the green quantum dot compositions of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 was measured. For example, the EHD ink jetting ability was evaluated by using an iEHD printer (ENJET) having a nozzle inner diameter of 75 μm.

[0200] In addition, the ink jetting ability of the red quantum dot compositions of Example 2-1 and Comparative Examples 2-1 and 2-2 was measured in the same manner. The results are shown in Tables 5A and 5B below.

[0201] Table 5A

[0202] Example 1-1 Example 1-2 Examples 1-3 Examples 1-4 Examples 1-5 Ink jetting capability good good good good good

[0203] Table 5B

[0204] Comparative Example 1-1 Comparative Example 1-2 Comparative Examples 1-3 Example 2-1 Comparative Example 2-1 Comparative Example 2-2 Ink jetting capability good Difference Difference good good Difference

[0205] It was confirmed that all the green quantum dot compositions exhibited good EHD inkjet printing performance of about 1.5kVΔ voltage -0.5kV to -2.0kV without nozzle clogging, and the red quantum dot compositions also exhibited good EHD inkjet printing performance of about 2.2kVΔ voltage -0.6kV to -2.8kV without nozzle clogging.

[0206] However, the quantum dot compositions of Comparative Examples 1-2, 1-3, and 2-2 having a viscosity of not more than 100 cp presented a problem in that jetting was not properly performed in a desired area during EHD printing due to the low viscosity.

[0207] The present disclosure is not limited to the above-described embodiments, and it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the present disclosure as defined by the appended claims.

[0208] Provided are a quantum dot composition having high viscosity suitable for EHD inkjet printing, excellent optical properties, and excellent ink jetting ability (jetting performance), a method for producing the same, a cured product of the quantum dot composition, and a display device including the same.

[0209] The quantum dot composition according to the present disclosure has excellent optical properties, high viscosity suitable for EHD inkjet printing, and excellent ink jetting ability (jetting performance).

[0210] Therefore, a light emitting element and a display device including the quantum dot composition according to the present disclosure may have excellent optical properties.

Claims

1. A quantum dot composition comprising: quantum dots; Photopolymerizable monomers; and Oligomers, The photopolymerizable monomer includes a compound including an aromatic ring.

2. The quantum dot composition according to claim 1, The aromatic ring-containing compound includes a phenoxy group, a phenol group or a phenyl group.

3. The quantum dot composition according to claim 1, The aromatic ring-containing compound includes phenoxyethyl acrylate, phenoxyethyl methacrylate, o-phenylphenoxyethyl acrylate, phenoxybenzyl acrylate, benzyl acrylate, benzyl methacrylate, biphenyl methyl acrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol A ethoxylate dimethacrylate, bisphenol A ethoxylate diacrylate, bisphenol A glycerol diacrylate, or bisphenol F ethoxylate diacrylate.

4. The quantum dot composition according to claim 1, The photopolymerizable monomer further comprises an acrylate-based monomer.

5. The quantum dot composition according to claim 1, The oligomer includes a compound containing a carbon-carbon double bond and a compound containing a thiol group.

6. The quantum dot composition according to claim 5, The compound containing a carbon-carbon double bond comprises one or more compounds containing a phenol group.

7. The quantum dot composition according to claim 1, Wherein the quantum dots are surface-modified by: a first ligand represented by the following formula 1; and a second ligand including 3 to 40 carbon atoms and including a carboxyl group: [Formula 1] In formula 1, M is a divalent to tetravalent metal, m is an integer of 1 to 4, each X is independently a C3-C20 organic group, and n is an integer from 2 to 4.

8. The quantum dot composition according to claim 1, The viscosity of the quantum dot composition is in the range of about 150 cp to about 600 cp at room temperature.

9. The quantum dot composition according to claim 1, The quantum dot composition is used for electrohydrodynamic inkjet printing.

10. A method for producing a quantum dot composition as claimed in any one of claims 1 to 4, the method comprising: modifying the surface of quantum dots and dispersing the quantum dots in a photopolymerizable monomer to obtain a quantum dot dispersion; as well as adding oligomers and photopolymerizable monomers to the quantum dot dispersion, The photopolymerizable monomer includes a compound including an aromatic ring.

11. The method according to claim 10, The aromatic ring-containing compound includes a phenoxy group, a phenol group or a phenyl group.

12. The method according to claim 10, The compound containing an aromatic ring is phenoxyethyl acrylate, phenoxyethyl methacrylate, o-phenylphenoxyethyl acrylate, phenoxybenzyl acrylate, benzyl acrylate, benzyl methacrylate, biphenyl methyl acrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol A ethoxylate dimethacrylate, bisphenol A ethoxylate diacrylate, bisphenol A glycerol diacrylate, or bisphenol F ethoxylate diacrylate.

13. The method according to claim 10, The photopolymerizable monomer further comprises an acrylate-based monomer.

14. The method according to claim 10, The surface modification of the quantum dots comprises: A primary surface modification is performed by adding a first ligand represented by the following Formula 1, and a secondary surface modification is performed by adding a second ligand including 3 to 40 carbon atoms and including a carboxyl group: [Formula 1] In formula 1, M is a divalent to tetravalent metal, m is an integer of 1 to 4, each X is independently a C3-C20 organic group, and n is an integer from 2 to 4.

15. The method according to claim 10, The surface modification of the quantum dots comprises simultaneously adding a first ligand represented by the following formula 1 and adding a second ligand comprising 3 to 40 carbon atoms and including a carboxyl group: [Formula 1] In formula 1, M is a divalent to tetravalent metal, m is an integer of 1 to 4, each X is independently a C3-C20 organic group, and n is an integer from 2 to 4.

16. The method of claim 10, The oligomer is prepared by mixing a compound comprising a carbon-carbon double bond and a compound comprising a thiol group.

17. The method of claim 16, The compound containing a carbon-carbon double bond comprises at least one compound containing a phenol group.

18. The method of claim 16, wherein the oligomer comprises a thermal initiator and a polymerization inhibitor, and The oligomer is prepared by stirring and polymerizing at room temperature before mixing with the quantum dot dispersion.

19. A cured film prepared by using the quantum dot composition according to any one of claims 1 to 9.

20. A light-emitting element comprising the quantum dot composition according to claim 1.

21. A display device comprising the light emitting element according to claim 20.

22. Display device, comprising: A light-emitting element, the light-emitting element comprising: A quantum dot composition, comprising: quantum dots; a photopolymerizable monomer; and Oligomers, in: The photopolymerizable monomer includes a compound including an aromatic ring, and The quantum dots are surface-modified by a first ligand represented by the following Formula 1 and a second ligand including 3 to 40 carbon atoms and including a carboxyl group: [Formula 1] Wherein in Formula 1, M is a divalent to tetravalent metal, m is an integer of 1-4, each X is independently a C3-C20 organic group, and n is an integer of 2-4.

Citation Information

Patent Citations

  • Color-convertible microlens array with fine printing of quantum dot / polymer composite and manufaturing method thereof

    KR1020200137977A

  • Gastric tube device and method of use

    KR1020230131930A